Psychosocial correlates of depression in paediatric patients with epilepsy in a teaching hospital in Nigeria - Enyidah, Nonyenim Solomon; Abazie, Chidubem Onyema; Nonye-Enyidah, Esther Ijeoma (International Journal of Research in Medical Sciences, 2024)
Background: Seizures are the most common paediatric neurological disorder with most children suffering at least one seizure before the age 16yr. The psychosocial comorbidities which adversely affect quality of life especially depression, are often neglected. This study sorts to highlight the psychosocial correlates of depression among these children. Methods: Recruitment was in a paediatric neurology clinic in a tertiary-level hospital. Children were eligible for recruitment if aged 9-18 and had a diagnosis of epilepsy as confirmed by a neurologist, in care for a period of more than 3 months, and parents gave consent. Children who met the study inclusion criteria were subjected to a two- stage interview process using CES and DICA-1V tools, designed to screen and confirm depression. These instruments have previously been validated on a Nigerian population. The study was cross section and descriptive, with psychometric evaluation p-values<0.05, statistically significant. Results: A total of 400 children were offered participation, and 380 were recruited, among them, 117 (30.8%) met the clinical criteria for major depression with 40 (10%) of them in need of urgent medical attention. Males were more depressed, p=0.000, OR: 0.861, respondents aged 9-11yr showed a strong association with depression p=0.001, OR: 1.911. Living arrangements of patients, p=0.001, OR: 0.632, family size (siblings), p=0.004, marital status of mothers, p=0.001, OR: 2.373, turned out significant with mothers’ marital status showing a strong association. Duration of illness and frequency of seizures, showed a very strong association with depression p=0.023, OR:1.203, and p=0.001, OR:1.411 respectively. Conclusions: The study highlights a strong association between effects of epilepsy and psychosocial wellbeing of children and the high risk posed by unstable family settings on children’s health.